Nucleotide polymorphism and copy number variant detection using exome capture and next‐generation sequencing in the polyploid grass Panicum virgatum. (11th August 2014) - Evans, Joseph; Kim, Jeongwoon; Childs, Kevin L.; Vaillancourt, Brieanne; Crisovan, Emily; Nandety, Aruna; Gerhardt, Daniel J.; Richmond, Todd A.; Jeddeloh, Jeffrey A.; Kaeppler, Shawn M.; Casler, Michael D.; Buell, C. Robin
Summary Switchgrass (Panicum virgatum) is a polyploid, outcrossing grass species native to North America and has recently been recognized as a potential biofuel feedstock crop. Significant phenotypic variation including ploidy is present across the two primary ecotypes of switchgrass, referred to as upland and lowland switchgrass. The tetraploid switchgrass genome is approximately 1400 Mbp, split between two subgenomes, with significant repetitive sequence content limiting the efficiency of re‐sequencing approaches for determining genome diversity. To characterize genetic diversity in upland and lowland switchgrass as a first step in linking genotype to phenotype, we designed an exome capture probe set based on transcript assemblies that represent approximately 50 Mb of annotated switchgrass exome sequences. We then evaluated and optimized the probe set using solid phase comparative genome hybridization and liquid phase exome capture followed by next‐generation sequencing. Using the optimized probe set, we assessed variation in the exomes of eight switchgrass genotypes representing tetraploid lowland and octoploid upland cultivars to benchmark our exome capture probe set design. We identified ample variation in the switchgrass genome including 1 395 501 single nucleotide polymorphisms (SNPs), 8173 putative copy number variants and 3336 presence/absence variants. While the majority of the SNPs (84%) detected was bi‐allelic, a substantial number was tri‐allelic with limited occurrence of tetra‐allelic polymorphisms consistent with the heterozygous and polyploid nature of the switchgrass genome. Collectively, these data demonstrate the efficacy of exome capture for discovery of genome variation in a polyploid species with a large, repetitive and heterozygous genome.